2015
DOI: 10.1364/oe.23.013880
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity refractive index sensor based on adiabatic tapered optical fiber deposited with nanofilm by ALD

Abstract: Atomic layer deposition (ALD) technology is introduced to fabricate a high sensitivity refractive index sensor based on an adiabatic tapered optical fiber. Different thickness of Al2O3 nanofilm is coated around fiber taper precisely and uniformly under different deposition cycles. Attributed to the high refractive index of the Al2O3 nanofilm, an asymmetry Fabry-Perot like interferometer is constructed along the fiber taper. Based on the ray-optic analysis, total inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…For most of the fiber-based refractometers, the response of the sensor to changes in surrounding refractive index (SRI) is nonlinear, in which the sensitivity is much higher for an SRI close to 1.45 (which is the fiber material refractive index), but lower for an SRI close to 1.33 [ 1 , 2 ]. In order to improve SRI sensitivity in the vicinity of an SRI of 1.33 (which is the environment refractive index of the most of biosensors), nanofilm-coated optical fibers with metallic materials, semiconductor materials or high refractive index dielectric materials have been widely investigated [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. One strategy is the deposition of high refractive index nanofilm on fibers which exhibit a mode resonant feature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For most of the fiber-based refractometers, the response of the sensor to changes in surrounding refractive index (SRI) is nonlinear, in which the sensitivity is much higher for an SRI close to 1.45 (which is the fiber material refractive index), but lower for an SRI close to 1.33 [ 1 , 2 ]. In order to improve SRI sensitivity in the vicinity of an SRI of 1.33 (which is the environment refractive index of the most of biosensors), nanofilm-coated optical fibers with metallic materials, semiconductor materials or high refractive index dielectric materials have been widely investigated [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. One strategy is the deposition of high refractive index nanofilm on fibers which exhibit a mode resonant feature.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the schemes based on fibers without mode resonant feature are developed, including adiabatic tapered optical fiber, D-shaped optical fiber, cladding-removed multimode optical fiber, etc. Depending on the properties of the nanofilm, these fiber-optic refractometers without mode resonance work based on either surface Plasmon resonance (SPR) [ 8 , 9 ] or lossy modes resonance (LMR) [ 10 , 11 , 12 , 13 ]. For SPR-based refractometers, the real part of the permittivity of the coated nanofilm is negative and higher in magnitude than both its own imaginary part and the permittivity of the material surrounding the nanofilm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has several kinds of common structures, including the core offset splicing [3,4] , material coating [5,6] , fiber grating [7,8] and so on. For example, Shan Zhu et al [9] introduced the atomic layer deposition technology to fabricate a high sensitivity RI sensor based on an adiabatic tapered optical fiber, where an asymmetric Fabry-Perot like interferometer is constructed along the fiber taper. Peter Tatar et al [10] proposed a modification structure model of in-fiber sensor based on intermodal interference in two core photonic crystal fibers for measuring external RI.…”
mentioning
confidence: 99%
“…For example, Yadav et al reported an RI sensor with a sensitivity of 1500 nm∕RIU based on a tapered single-mode fiber [11]. Most recently, Zhu et al developed a highly sensitive RI sensor with a sensitivity of 6008 nm∕RIU by coating a Al 2 O 3 nanofilm on a tapered fiber [12]. Xu et al have demonstrated an RI sensor with a sensitivity of 6523 nm∕RIU based on cascaded microfiber knot resonators (CMKRs) with Vernier effect [13].…”
mentioning
confidence: 99%